2022
DOI: 10.1073/pnas.2204666119
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the reaction kinetics in aprotic lithium-carbon dioxide batteries with unconventional phase metal nanomaterials

Abstract: Given the high energy density and eco-friendly characteristics, lithium-carbon dioxide (Li-CO 2 ) batteries have been considered to be a next-generation energy technology to promote carbon neutral and space exploration. However, Li-CO 2 batteries suffer from sluggish reaction kinetics, causing large overpotential and poor energy efficiency. Here, we observe enhanced reaction kinetics in aprotic Li-CO 2 batteries with unconventional phase 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Second, in the synthesis process, heterophase or unusual phase metal catalysts are becoming attractive, and how to combine them with the appropriate 2D nanomaterials has rarely been explored. [103][104][105]154 Currently, the difficulty mainly lies in obtaining sufficient samples and a certain purity of unconventional phase catalysts. Third, there have been increasing reports on tandem catalysts, such as one metal that produces CO (e.g., Ag and Au) working together with another metal such as Cu to increase the yield of C 2+ products in CO 2 RR.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the synthesis process, heterophase or unusual phase metal catalysts are becoming attractive, and how to combine them with the appropriate 2D nanomaterials has rarely been explored. [103][104][105]154 Currently, the difficulty mainly lies in obtaining sufficient samples and a certain purity of unconventional phase catalysts. Third, there have been increasing reports on tandem catalysts, such as one metal that produces CO (e.g., Ag and Au) working together with another metal such as Cu to increase the yield of C 2+ products in CO 2 RR.…”
Section: Discussionmentioning
confidence: 99%
“…523,528–530 In our recent work, we synthesized an unconventional 4H/fcc phase of Ir nanostructure grown on 4H/fcc Au nanorods (Au@4H/fcc-Ir 0.14 ) as the cathode catalyst for aprotic Li–CO 2 batteries. 531 Through advanced structure characterizations with both spherical aberration-corrected STEM (Fig. 30a–c) and XAS, the unusual phase Ir was confirmed to be epitaxially grown on 4H/fcc Au nanorods.…”
Section: Energy-related Applications Of Defective 2d Materialsmentioning
confidence: 93%
“…47,75,109,143,145−149 Lately, Zhou et al have reported a novel unconventional phase 4H/facecentered cubic (fcc) Ir nanostructures on Au NRs (denoted as Au@4H/fcc-Ir) that could boost the reaction kinetics of aprotic Li−CO 2 batteries. 75 The unconventional phase 4H/fcc Ir nanostructures were grown on 4H/fcc Au NRs by the controlled growth of Ir in a wet-chemical route. In brief, a 1.5 mL ethanolic dispersion of cleaned 4H/fcc Au NRs was prepared and marked as solution-I.…”
Section: Cathode Catalysts Involving Noble Metals and Their Compoundsmentioning
confidence: 99%
“…At the same time, no discernible change occurred to the WT contour plots obtained from Au L 3 -edge EXAFS data, vindicating structure preservation of 4H/fcc Au after Ir deposition. Zhou et al 75 used the Au@4H/fcc-Ir 0.14 nanostructures as the catalytic gas cathode in Li−CO 2 batteries (1 M LiTFSI in DMSO with 0.3 M LiNO 3 as electrolyte). For comparison with pure fcc-Ir catalyst, they made controlled cathodes by physically mixing 4H/fcc Au NRs and fcc Ir NPs in an 86:14 weight ratio (denoted as Au + fcc-Ir 0.14 ).…”
Section: Cathode Catalysts Involving Noble Metals and Their Compoundsmentioning
confidence: 99%